Hubungan Motivasi Kerja Perawat Dengan Perilaku Caring Perawat Pelaksana Di Ruang Rawat Inap Rumah Sakit Umum Wisma Prashanti Tabanan - I Gusti Agung Ayu Sherlyna Prihandhani; Alfiery Leda Kio (Interest : Jurnal Ilmu Kesehatan, 2019)
Background: Caring behavior is the main focus act in nursing practice which contains humanistic values, a responsive attitude, and responsible for fulfilling patients’ expectations. The results of the patient satisfaction survey and observation result showed the lack of caring behavior of the attending nurses in Inpatient Ward of Wisma Prashanti General Hospital. This study aimed at determining the relation of nurses’ working motivation towards caring behavior of attending nurses in Inpatient Ward of Wisma Prashanti General Hospital Tabanan. Methods: The design of this study was cross-sectional using a quantitative approach. Data was collected by filling out questionnaires by 37 of attending nurses from Juni-August 2018 in Inpatient Ward of Wisma Prashanti General Hospital Tabanan. Data analysis included univariate and bivariate analysis with Kendall's Tau_b test. Result: Univariate analysis showed that most nurses had the high working motivation (89.2%) and had good caring behavior (91.9%). Bivariate analysis showed a significant relationship between working motivation and caring behavior of attending nurses in Inpatient Ward of Wisma Prashanti General Hospital Tabanan (p = 0,00). Conclusion: Fulfillment of the supporting factors of nurses’ working motivation is needed to maintain or improve the working motivation of nurses, therefore, nurses have an inner impulse to provide caring in order to provide optimal and professional nursing care.